Fundamentals of business process management - Dumas, Marlon (Berlin : Springer, 2013)
Business Process Management (BPM) is the art and science of how work should be performed in an organization in order to ensure consistent outputs and to take advantage of improvement opportunities, e.g. reducing costs, execution times or error rates. Importantly, BPM is not about improving the way individual activities are performed, but rather about managing entire chains of events, activities and decisions that ultimately produce added value for an organization and its customers.
Includes bibliographical references : p. (385-389) and index.
Keywords: Business -- Data processing -- Management; Reengineering (Management).